Distinct Factors Shape Aquatic and Sedimentary Microbial Community Structures in the Lakes of Western China - Yang, Jian; Jiang, Hongchen; Wu, Geng; Liu, Wen; Zhang, Guojing (Frontiers in Microbiology, 2016)
Little is known about the relative importance of spatial and environmental factors to structuring aquatic and sedimentary microbial biogeography in lakes. Here, we investigated the microbial community composition (MCC) of the water (n = 35) and sediment (n = 35) samples from 16 lakes in western China (salinity: freshwater to salt saturation; pairwise geographical distance: 9 - 2027 km) using high-throughput sequencing and evaluated the relative importance of spatial and environmental factors to microbial (including total, abundant and rare) distributions. Our results showed that spatial factors were more important than environmental factors in shaping the biogeography of aquatic and sedimentary microbial communities in the studied lakes, and spatial factors on abundant microbial community was stronger than that on the total/rare microbial communities. Moreover, sedimentary rare MCC might be more sensitive to environmental factors than its aquatic counterpart. Such different biogeography responses of total, abundant and rare communities to environmental and spatial factors could be ascribed to different physiochemical properties between water and sediment. Collectively, this study expands our understanding of factors shaping microbial biogeography of total, abundant and rare communities between waters and sediments of lakes.